A queer futurity autofantasía: contouring discourses of Latinx through memory and queer youth literature. Issue 3 (3rd July 2019) - Moreman, Shane T.
ABSTRACT: This communication-centered performance studies analysis forefronts Latinx positionality in three key childhood moments to offer examples of queer futurity. An autofantasía presented through performative writing, the research essay brings Latinx into embodied practice via the memories of queer childhood, the themes of queer youth literature, and the contemporary understandings of Latinx. From the vantage points of my four-year-old self, my nine-year-old self, and my fourteen-year-old queer self, I draw upon queer and latinidad themes found in three separate queer children's books. All analyses combine to contour, for the moment, the changing discursivity of Latinx as a queer futurity.